Author Correction: Distinct fibroblast subsets drive inflammation and damage in arthritis (Nature, (2019), 570, 7760, (246-251), 10.1038/s41586-019-1263-7) - Croft, Adam P.; Campos, Joana; Jansen, Kathrin; Turner, Jason D.; Marshall, Jennifer; Attar, Moustafa; Savary, Loriane; Wehmeyer, Corinna; Naylor, Amy J.; Kemble, Samuel; Begum, Jenefa; Dürholz, Kerstin; et al. (Nature, 2025)
Correction to: Naturehttps://doi.org/10.1038/s41586-019-1263-7 Published online 29 May 2019 In the version of this article initially published, in the legend of Extended Data Fig. 6, “SL fibroblasts correspond to F1–F4 fibroblast subsets and are PDPN+THY1−” should have read “SL fibroblasts correspond to F1–F4 fibroblast subsets and are PDPN+THY1+”. Due to the age of the article, the caption cannot be updated directly; this amendment serves to correct the article.
CRIS-Team Scopus Importer:2025-12-26